FAKTOR PENYEBAB PERSELINGKUHAN SUAMI ISTRI DAN UPAYA PENANGANANNYA DI KUA KECAMATAN RUPAT - Muhammad Al Mansur; Saim Saim; Rino Riyaldi (IAIN Ambon, 2021)
The case of infidelity has recently become the subject of an interesting and widespread conversation, because infidelity itself is not only dominated by men, but also women in all walks of life and classes. This phenomenon does not only occur in big cities but also in small and isolated cities, such as in Rupat sub-district, Bengkalis district. This then raises the question What are the faktors that cause an infidelity between husband or wife in office of religious affairs (KUA) Rupat sub district, how are the efforts to handle the affair case at there, what is the perspective of Islamic law and Malay customary law on the case of infidelity. This study using qualitative and library research. Data collection techniques used were observation, interviews and documentation with qualitative descriptive analysis techniques. The faktors causing an affair in Rupat sub district, the first is, internal faktors which is consist of cultural differences, disappointment, dissatisfaction in sexual life, insufficient finansial needs. The second is external faktor, which is of the influence of close friends, closeness to other types of friends, erotic-sexual temptations. The method of handling performed by KUA Rupat is to Implement Pre-Marriage Guidance and Post-Marriage Guidance. The infidelity in islamic law can be categorized into majazi adultery and actual adultery, depending on the extent of the behavior and actions of the person committing of the infidelity. While Malay customary law in Bengkalis see this affair set off from philosophy